2013
DOI: 10.1111/famp.12032
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Attributions for Late‐Life Depression and Their Associations with Caregiver Burden

Abstract: Late-life depression (LLD) has detrimental effects on family caregivers that may be compounded when caregivers believe that depressive behaviors are volitional or within the patient’s capacity to control. In this study we examined three person-centered caregiver attributions that place responsibility for LLD on the patient (i.e., character, controllability, and intention), and the impact of such attributions on levels of general caregiver burden and burden specific to patient depressive symptoms. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Factors that affect the mental health and coping of caregivers have recently begun to receive considerable attention (Gelkopf & Roe, ; Hernandez, Barrio, & Yamada, ; Polenick & Martire, ; Zhou & Yi, ). Financial burden is an important factor which contributes to mental health problems of caregivers of children with asthma.…”
Section: Overview Of the Present Studymentioning
confidence: 99%
“…Factors that affect the mental health and coping of caregivers have recently begun to receive considerable attention (Gelkopf & Roe, ; Hernandez, Barrio, & Yamada, ; Polenick & Martire, ; Zhou & Yi, ). Financial burden is an important factor which contributes to mental health problems of caregivers of children with asthma.…”
Section: Overview Of the Present Studymentioning
confidence: 99%
“…In a review of research involving next-of-kin who provided care for patients with chronic illnesses it was found that they were at risk of caregiver burden, which could result in depression, social isolation, and financial stress [26]. Stress and depressive symptoms were also found when examining caregiver burden among next-of-kin in palliative care [6], as well as next-of-kin to patients with late-life depression [27]. Being next-of-kin in palliative care is complex and demanding; it comprises changing roles and novel practical and emotional challenges [28].…”
Section: Discussionmentioning
confidence: 99%
“…c 30 LLD patients and their primary caregivers in the trial group, and 30 LLD patients and caregivers in the control group. 4. Amos version 22.0 statistical software will be used for SEM of the risk factors for LLD.…”
Section: Correlation Analysis Logistic Regression (For Binary Variabmentioning
confidence: 99%
“…Late life depression (LLD) is complex, burdensome, and difficult to treat. Specifically, it refers to elderly people who, for the first time in their lives, meet criteria for major depressive disorder (MDD) or display clinically significant depressive symptoms such as functional disability, cognitive decline, increased risk of medical comorbidity (e.g., co-dementia), and even suicide in severe cases (1)(2)(3)(4). Meanwhile, MDD in the elderly, as defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV TR), has been a growing public health concern, and it is projected to be the second leading cause of disease by the year 2020 (5,6).…”
Section: Introductionmentioning
confidence: 99%